Mutations in TUBG1, DYNC1H1, KIF5C and KIF2A cause malformations of cortical development and microcephaly - Poirier, Karine; Lebrun, Nicolas; Broix, Loic; Tian, Guoling; Saillour, Yoann; Boscheron, Cécile; Parrini, Elena; Valence, Stephanie; Pierre, Benjamin Saint; Oger, Madison; Lacombe, Didier; Geneviève, David; et al. (Nature genetics, 2013)
Jamel Chelly, Nicholas Cowan and colleagues report mutations in TUBG1 , DYNC1H1 , KIF2A and KIF5C in individuals with malformations of cortical development and microcephaly. Their findings emphasize the importance of centrosomal and microtubule-related proteins for normal brain development. The genetic causes of malformations of cortical development (MCD) remain largely unknown. Here we report the discovery of multiple pathogenic missense mutations in TUBG1, DYNC1H1 and KIF2A , as well as a single germline mosaic mutation in KIF5C , in subjects with MCD. We found a frequent recurrence of mutations in DYNC1H1 , implying that this gene is a major locus for unexplained MCD. We further show that the mutations in KIF5C, KIF2A and DYNC1H1 affect ATP hydrolysis, productive protein folding and microtubule binding, respectively. In addition, we show that suppression of mouse Tubg1 expression in vivo interferes with proper neuronal migration, whereas expression of altered γ-tubulin proteins in Saccharomyces cerevisiae disrupts normal microtubule behavior. Our data reinforce the importance of centrosomal and microtubule-related proteins in cortical development and strongly suggest that microtubule-dependent mitotic and postmitotic processes are major contributors to the pathogenesis of MCD.